Acute Toxicity and Antioxidant and Antibacterial Activities of Kyllinga polyphylla Willd. ex Kunth, Cyperaceae Family - Van-Ay Nguyen; Thi-Hang Phung; Thi-Diem-Trang Kieu; Trong-Hong-Phuc Nguyen (Journal of Toxicology)
Kyllinga polyphylla Willd. ex Kunth. (KP) is a wild herb commonly distributed in the Mekong Delta, Vietnam. This study was carried out to evaluate the antibacterial and antioxidant activities and acute toxicity of KP before conducting studies at the in vivo level. All parts of KP had the free radical scavenging capacity of DPPH, in which the root methanol extract had the best antioxidant capacity (EC50 = 9.54 ± 0.37 μg/mL). Most of the extracts had a wide range of antibacterial spectra. The methanol and ethanol extracts (200 mg/mL) have ability to resist eight common bacterial strains (including Staphylococcus aureus, Listeria innocua, Bacillus subtilis, Bacillus cereus, Escherichia coli, Salmonella sp., Pseudomonas aeruginosa, and Enterococcus faecalis), which is equivalent to the antibacterial activity of amoxicillin and tetracycline at a concentration of 1 mg/mL. KP extracts did not cause death at a dose of 5000 mg/kg body weight and did not significantly change the biochemical, hematological, as well as histological structures of internal organs in toxicity-tested mice in comparison with the control. The research results showed that KP should be more interested in research that supports disease treatment, synthetic extraction of antibiotics, or other in vivo studies.